Radicalización política en el campo de la derecha. - Carnagui, Juan (Universidad Nacional del Litoral, 2020)
The trajectory made by the CNU from its origins, in 1965, until the last active group of the organization was deactivated, in April 1976, allows us to visualize the path that led from university militancy in the Peronist "new right" to parastatal repression. In this article we analyze, from a local perspective, the elements that allowed this transit in a key that combines the particularities of the organization with the impact of the process of political radicalization characteristic of this period, which also had an impact on the right-wing tradition. In turn, we seek to highlight the peculiar way in which the CNU joined the parastatal repressive plot. Far from proposing a generalization based on this experience, this work aims to complex the the map of political organizations allowing, at the same time, to visualize the local peculiarities of the repressive actions developed by the group